Role of management control to steering the performance of the economic business - Namoun, Azzedine (Finance and Business Economies Review, 2020)
This article aims to present the methodology for developing provisional budgets and the people involved in their preparation, and how they are implemented by the members of the organization and what are the actions to be taken in case of deviation from the Goals. We found through this study that the provisional budgets contribute to steering the performance of the organization through the translation of strategic objectives into annual objectives and by preparing action plans to achieve them. Also, budgetary control helps correct any deviations that may arise from the objectives.